Equilibrium calculation during deposition of nitride films in Nb-N-Cl-H system. Raschety ravnovesij pri osazhdenii nitridnykh plenok v sisteme Nb-N-Cl-H - "Gorbov, S I"; "Petrusevich, I V"; "Ogurtsov, S V [Moskovskij Meditsinskij Stomatologicheskij Inst., Moscow (Russian Federation) Gosudarstvennyj Nauchno-Issledovatel'skij i Proektnyj Inst. Redkometallicheskoj Promyshlennosti, Moscow (Russian Federation)]" (1991)
Equilibria in Nb-N-Cl-H system are calculated with an account 29 components in condensed and gaseous states, including 6 niobioum nitride phases. Residue phase diagrams by deposition of niobium nitrides from vapour-gas mixture and diagrams of residue equilibrium compositions as function of the mentioned parameters, which enabled determination of the deposition process optimal regime for [epsilon]-NbN pure phase are plotted.
Keywords: "36 MATERIALS SCIENCE"; "NIOBIUM COMPOUNDS"; "CHEMICAL VAPOR DEPOSITION"; "PHASE DIAGRAMS"; "NITRIDES"; "CHLORIDES"; "FILMS"; "HYDRIDES"; "NUMERICAL SOLUTION"; "PHASE STUDIES"; "THERMODYNAMIC PROPERTIES"; "CHEMICAL COATING"; "CHLORINE COMPOUNDS"; "DEPOSITION"; "DIAGRAMS"; "HALIDES"; "HALOGEN COMPOUNDS"; "HYDROGEN COMPOUNDS"; "NITROGEN COMPOUNDS"; "PHYSICAL PROPERTIES"; "PNICTIDES"; "REFRACTORY METAL COMPOUNDS"; "SURFACE COATING"; "TRANSITION ELEMENT COMPOUNDS"; "360202* - Ceramics, Cermets, & Refractories- Structure & Phase Studies"; "360606 - Other Materials- Physical Properties- (1992-)"